The effectiveness of deductive, inductive, implicit and incidental grammatical instruction in second language classrooms - Tammenga-Helmantel, Marjon; Arends, Enti; Canrinus, Esther T. (System (Linköping), 2014)
This quasi-experimental study compares the effectiveness of deductive, inductive, implicit and incidental grammar instruction and investigates to what extent complexity influences these results. A total of 981 Dutch students in lower secondary education learning German, English or Spanish as a second language participated in this experiment. The design of the study consisted of a pre-test, a series of lessons about the degrees of comparison and a post-test. Both meta-linguistic knowledge and production of the grammatical structure were tested. By using analysis of variance, differences in students' test scores between instruction forms were examined. The findings show that any kind of grammar instruction (explicit and non-explicit forms) is more effective than no grammar intervention/exposure. Furthermore, complexity of the grammatical structure does not influence the effectiveness results.